Application of geographic information system in water quality study on a road construction project - Abdul Razak, Noorazlinda (2009)
According to the Malaysian Department of Environment’s (DOE) Water Quality Index for 2005, 52 river basins were polluted. Non point source pollution is a major pollution that has been affecting the quality of these river basins. It has been considered as the major pollution for river as the source can come from anywhere. But one of the most significantly of nonpoint sources is from the combined effects of land disturbances to construct new developments during construction activity. A study is conducted on a road construction project in Labis, Segamat to assess the non-point source pollution level through GIS. This study is done by generating the river network for the area in order to estimate the pollution loads. Rainfall and runoff are the components that are able to transport the pollution from one place to another. As the non-point source pollution is a diffused matter transported from land to river, the determining factors include the land use and soil type. A GIS software, ArcGIS 9.2 was used to produce the Digital Elevation Model (DEM) to generate a river network. With the aid of the 3D extension, visualization for the terrain produced was enhanced. The generated river was overlaid with the land use and geological map and interpolates with the WQI data from the sampling to estimate the loads of pollution. Expected Mean Concentration (EMC), which is associated with the land use, were used in this study to produce the pollutant load. Based on the final Pollutant Accumulated Loading Map, the total annual loading through the outlet of the river are 1940, 471, 595 and 1396 kg/year for total BOD, total TSS and NH3N, respectively. This project also demonstrates that Geographical Information System (GIS) fits in the role with its analytical operations of spatial and non-spatial information to identify and solve the pollutant loading in this construction area.